Synergistic oxygen substitution and heterostructure construction in polymeric semiconductors for efficient water splitting. Issue 25 (18th June 2020) - Chen, Li; Wang, Yuze; Wu, Chongbei; Yu, Guanhang; Yin, Yue; Su, Chenliang; Xie, Jijia; Han, Qing; Qu, Liangti
Abstract : A synergistic oxygen substitution and heterostructure construction strategy was developed to synthesize oxygenated-triazine-heptazine-conjugated polymer nanoribbons for photocatalytic water splitting. Abstract : Herein, we present a synergistic oxygen-substitution and heterostructure construction strategy to produce a two-dimensional oxygenated-triazine-heptazine-conjugated carbon nitride nanoribbon (TOH-CN). The TOH-CN was proved to have an internal donor–acceptor heterostructure that could promote interfacial charge separation and transport, while the oxygen substitution effect modulated the nanoribbon morphology with increased surface/edge active sites and tuned the electronic structure to extend visible-light absorption as well as to improve band structure alignment. Benefiting from these advantages, the TOH-CN served as an efficient bifunctional photocatalyst for both H2 and O2 evolution under visible-light irradiation, exhibiting a 16 times higher photocatalytic H2 evolution rate than that of its melon-based carbon nitride (g-C3 N4 ) counterpart, and a remarkable apparent quantum yield of 7.9% at 420 nm. The O2 evolution rate was 6 times higher than that of g-C3 N4, even much higher than those of most bifunctional carbon nitride-based photocatalysts. The developed synergistic strategy of oxygen substitution and heterostructure construction will provide an alternative route for the synthesis of efficient polymeric semiconductors toward efficient solar-to-chemical conversion.